Maximal lipidic power in high competitive level triathletes and cyclists - Gonzalez-Haro, C.; Galilea, P. A.; Gonzalez-de-Suso, J. M.; Drobnic, F.; Escanero, J. F.; Chander, M. (British Journal of Sports Medicine, 2007)
Objective: To describe the fat-oxidation rate in triathlon and different modalities of endurance cycling.